Morphological Characteristics and Kinship Relationship of Mushroom Schizophyllum commune Fr. - Kusrinah Kusrinah; Rina Sri Kasiamdari (Journal of Natural Sciences and Mathematics Research, 2015)
Schizophyllum commune is a mushroom from the division of Basidiomycota which abundance at rainy season on wood that have been moldered for its habitat. S. commune has been distributed widely at various types of wood habitat (jack fruit, bamboo, rubber, mango etc). Existence of this mushroom has not been known as well as any mushroom are able to be consumed/edible yet. In Java, the societies who have known it as consumption mushroom called it with local name jamur gigit. Jamur gigit is potential to become food material and based on organoleptic test indicates that jamur gigit is more delicious from oyster mushroom. The purpose of research is to investigate the morphology character of S. commune at various growth phases and to study the S. commune relationship in Java. The result of this research is expected can give information about morphology character of S. commune in each its growth phase and to understand S. commune relationship in Java. Sample for research has been collected in 3 areas in Java. The macroscopic morphology character and microscopic character of S. commune were observed. The character that had been obtained is used to compile description and be analyzed by cluster using SPSS 13.0 to study the kinship relationship. The result of research indicates that morphology character of S. commune in Java of fruit body when old and young phase was different, while the microscopic character almost same to the obtained sample. The result of analysis cluster indicated that at similar level of 38,1 % there were two clusters, first cluster was Sidoarjo a S. commune and S. commune Yogyakarta. The second cluster has member the Sidoarjo b S. commune, Malang S. commune, Tangerang S. commune, Semarang S. commune and Kuningan S. commune. © 2015 JNSMR UIN Walisongo. All rights reserved.